The Evolution of Organized Crime at the National Level and Citizen Security - Pacheco Reyes, Wilson Francisco (2024)
One of the phenomena that has evolved in recent years is national and international organized crime, which is more violent every day, generating a climate of insecurity among people; In this sense, this work had the objective of "Analyzing the evolution of organized crime at the national level and its impact on citizen security." A qualitative approach was used, phenomenological design, performing a bibliographic review and journalistic data. As a result, it was established that crime, citizen insecurity and the perception of insecurity have increased in recent times. It was concluded that public security policies and justice operators do not have the expected achievements in the fight against this phenomenon at the national level.